Assessment of MICE Project Score Based on Greenship Rating of the Green Building Council of Indonesia - Sutikno Sutikno; Albert Eddy Husin; Maria Magdalena Enny Yuliatti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Regulation of the Minister of PUPR no. 21 of 2021 concerning green buildings which are mandatory for new buildings. MICE is a building used for Meetings, Incentives, Conventions, Exhibition activities. Green ship is a green building certification system in Indonesia at the design, construction, and operation stages. The research objective is to find out the most influential factors in achieving green ship for a platinum rating. Findings, there is an additional cost of IDR 140,302,830,412 as green costs but can be paid back within 6 years and 11 months. The novelty is the most influential factor in achieving a platinum rating in green ship as green costs with a reasonable payback period for a new building.